2022
DOI: 10.1186/s12913-022-07637-8
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Health based physical activities co-production policies towards cardiovascular diseases prevention: findings from a mixed-method systematic review

Abstract: Background Cardiovascular disease (CVD) is the first cause of death globally, with huge costs worldwide. Most cases of CVD could be prevented by addressing behavioural risk factors. Among these factors, there is physical and amateur sports activity (PASA), which has a linear negative correlation with the risk of CVD. Nevertheless, attempts to encourage PASA, as exercise prescription programmes, achieved little impact at the community-wide level. A new frontier to promote PASA is represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…Another recent review reported on patient active involvement and the use of m-health in supporting physical activity and co-production of health policies aiming at CVD prevention. Findings from that review indicated that patients (and beneficiaries) participations in interventions co-design process, though recognized as fundamental for CVD prevention, were lacking [ 20 ]. Our study had employed citizen science and co-design approaches to facilitate multi-level stakeholders’ engagement, participatory learning, adaptation of tools, and support co-creation of knowledge, and advocacy for social action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent review reported on patient active involvement and the use of m-health in supporting physical activity and co-production of health policies aiming at CVD prevention. Findings from that review indicated that patients (and beneficiaries) participations in interventions co-design process, though recognized as fundamental for CVD prevention, were lacking [ 20 ]. Our study had employed citizen science and co-design approaches to facilitate multi-level stakeholders’ engagement, participatory learning, adaptation of tools, and support co-creation of knowledge, and advocacy for social action.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic and scoping reviews have indicated the appropriateness of using a codesign or co-production approach to designing health-related programmes [ 17 , 19 ], and to promote health policies focusing on CVD prevention [ 20 ]. Citizen science and co-design approaches have been used to facilitate stakeholders’ engagement, participatory learning, adaptation of tools/processes, co-creation of knowledge, and advocacy for social action [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most bibliometric reviewers summarized literature subsets defined by eHealth user needs: promoting physical activity, healthy eating, and weight loss [9][10][11][12], preventing substance use [13], and providing e-mental health during the Covid-19 pandemic [14]. In addition, researchers reviewed digital technologies for health behavior change [15] and eHealth tools for anticoagulation management after cardiac valve replacement [16].…”
Section: Affiliations Introductionmentioning
confidence: 99%
“…Technology-focused bibliometric reviews assessed literatures on technology adoption [23], telehealth [24], the internet of things [25], telemedicine in rural areas for cost-effective and sustainable healthcare [26], mobile health as a means of involving citizens and public agencies in cardiovascular diseases prevention [27], and artificial intelligence adoption by healthcare organizations [28].…”
Section: Affiliations Introductionmentioning
confidence: 99%